Motivational climate in school sport and adolescent mental health: a systematic review - Yuan Wei; Guan-Nan Lai; Cheng Ji; Xiao-Ming Yang; Chun-Yuan Tie (Frontiers in Psychiatry, 2026)
Background Motivational climate in school-based physical education and sport represents a potentially modifiable context for adolescent mental health; however, its associations with psychological outcomes have not been systematically synthesised. This review aimed to synthesise evidence on perceived motivational climate and adolescent mental health outcomes in school settings. Methods Databases were searched from the inception to May 2026 following PRISMA guidelines. Inclusion criteria for studies included sampling of adolescents (10–19 years of age), assessment of motivational climate in school-based sport or physical education, reporting of psychological outcomes, and quantitative or mixed-method designs with original data. The JBI critical appraisal tools were used to appraise methodological quality. Findings were narratively synthesised because of the heterogeneity of the study designs, measurements and outcomes. Results A total of 19 studies were included with a total of 17, 825 adolescents across 8 countries. The quality of sixteen studies was high and three were rated as moderate. Across the included studies, task-involving, caring and empowering climates were generally associated with positive mental health outcomes such as subjective well-being, self-esteem, enjoyment, positive affect, and social-emotional competence. However, climates that were ego-involving and disempowering were associated with higher anxiety, depression, perceived stress, and shame. Multiple psychological, relational, cognitive, and behavioural explanatory pathways were identified, including basic psychological need satisfaction, intrinsic motivation, teacher-student and peer relationships, deliberate rumination, and physical education engagement. Conclusions The available evidence suggests that task-involving, caring, and empowering climates in school sport are generally associated with better adolescent mental health, whereas ego-involving and disempowering climates are associated with more anxiety, depression, stress, and shame. These associations may be partially explained by more than just basic psychological need satisfaction. Intrinsic motivation, supportive teacher-student and peer relationships, and even deliberate rumination also play a role. In short, how the sport climate meets adolescents’ psychological and social needs matters. Although causal inferences are precluded by the predominantly cross-sectional design of the included studies, shifting PE away from rigid competition and towards effort and mutual support could represent a practical approach to protect youth mental health. Systematic review registration https://www.crd.york.ac.uk/prospero/ , identifier CRD420261419406.